Tradisi Haul K.H Muhammad Zarkasyi Di Cibaduyut Tahun 2011 - 2022 - Gina Mahmudah (Priangan: Journal of Islamic Sundanese Culture, 2025)
The cycle of human life in general, starting from the womb, giving birth, getting married to facing death, is often held in traditions or rituals. In this study, the author will discuss the traditions that are carried out when facing death. Someone who is facing death, the family he left behind will carry out the tahlilan tradition of 7 consecutive days, 40 days (matangpuluh), and 100 days (natus). In the year after death, a haul tradition or one-year anniversary of death will be held. The Cibaduyut area is an area that still holds haul traditions to commemorate the death of K.H Muhammad Zarkasyi, a charismatic cleric and leader of the Cibaduyut Islamic boarding school. So, to commemorate his services every year his death is always commemorated. The method used in this study is the historical research method which includes four stages, namely the heuristic, criticism, interpretation, and historiography stages. The results of the study show that the haul tradition of a cleric feels more religious and flamboyant like that carried out in Cibaduyut. In addition, during the development of the Cibaduyut haul tradition, it experienced a cultural touch from the habaib circles. The implementation of the haul tradition also forms solidarity between communities and it can also be said that haul is a social reality because the community accepts the existence of the haul tradition.